Resistir é preciso: a memória de professores sobre a militância e a repressão política no Paraná (1964-1984). - Peron, Andreia (2014)
The proposal of this research refers to the analysis of the political participation, the militancy and repression suffered by teachers of Paraná state, in the period corresponding to the civil-military post-coup in 1964, which led the military to remain for 21 years in power. The space-temporal clipping refers to the State of Paraná in the period of 1964-1984. To achieve the objective of this work it was used a diverse bibliography of data collected by the Department of public file of Parana state(DEAP)with respect to documents produced by the political and Social Order from Police of Paraná (DOPS/PR), as also interviews done with former politicians militants who had the characteristic of being teachers at that time. The memory of these teachers was marked in this work with the theoretical-methodological contribution that was appropriated from the history of present time and oral history so that (memory) contribute to the ongoing construction of this part of Brazilian history.